UJI AKTIVITAS ANTIOKSIDAN DARI BIJI KOPI ROBUSTA (Coffea canephora P.) BERDASARKAN PERBEDAAN EKOLOGI DATARAN TINGGI DI PULAU JAWA - Novi Fajar Utami; Nhadira Nhestricia; Sri Maryanti; Tien Tisya; Siti Maysaroh (FITOFARMAKA: Jurnal Ilmiah Farmasi, 2018)
Robusta coffee contains alkaloids, flavonoids, saponins, tannins, caffeine and phenols. Phenol compounds in coffee have activity as an antioxidant. Robusta coffee beans grown in the area of Bandung, Bogor and Garut, West Java is known to have a unique characteristics and distinctive flavors. The difference in chemical characteristics of plant compounds  is caused by the agroecological differences (climate and altitude). Pangalengan area (Bandung) has a height of 817 AMSL, Cariu (Bogor) has a height of 680 AMSL mdpl and Cikeris (Garut) has a height of 900 AMSL mdpl. The purpose of this study was to determine the phytochemical characteristics and antioxidant activity of robusta roasting coffee beans grown in these three areas. Phytochemical characteristics were performed qualitatively and antioxidant activity was performed by DPPH method (2,2-diphenyl-1-picrylhydrazyl). The results of phytochemical characteristics test showed that the extract of robusta coffee bean from Bandung, Bogor and Garut contain alkaloid, flavanoid, saponin and tannin. The extract of robusta coffee from Bandung, Bogor and Garut showed significantly different antioxidant activity based on results of variance analysis statistical test with IC50 value of each achieved at concentrations of 55.13 ppm, 56.48 ppm, and 54.14 ppm. It can be concluded that robusta coffee extract from Garut has the highest antioxidant level compared with antioxidant activity of robusta coffee from Bandung and Bogor.